1996
DOI: 10.1037/0735-7028.27.1.83
|View full text |Cite
|
Sign up to set email alerts
|

The impact of multicultural training on White racial identity attitudes and therapy competencies.

Abstract: This exploratory investigation assessed changes in perceived multicultural therapy competencies and level of White racial identity development following a multicultural course. Results indicate that completion of a diversity-related course appeared to increase trainees' multicultural therapy competencies and to facilitate the adoption of more sophisticated White racial identity ego statuses; these changes remained stable at a 1-year follow-up. Findings from the qualitative analyses underscore the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
162
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(172 citation statements)
references
References 25 publications
10
162
0
Order By: Relevance
“…With respect to affective learning, we found that short-term attitudes (e.g., Rudman, 2001) were the most studied outcomes of diversity training (N ϭ 55), and 21 studies reported long-term effects for affective or attitudinal learning. There was some evidence suggesting that the changes in attitudinal learning could persist over 6 months (Thomas & Cohn, 2006) and deteriorate after 1 year (Hogan & Mallott, 2005;Neville, Heppner, Louie, Thompson, Brooks, & Baker, 1996). Turning to behavioral learning, we found that 37 studies reported short-term effects (e.g., Hauenstein et al, 2010), whereas 18 studies focused on long-term behavioral consequences of diversity training (e.g., Kalev et al, 2006;Roberson et al, 2009).…”
Section: Diversity Training Outcomesmentioning
confidence: 76%
See 1 more Smart Citation
“…With respect to affective learning, we found that short-term attitudes (e.g., Rudman, 2001) were the most studied outcomes of diversity training (N ϭ 55), and 21 studies reported long-term effects for affective or attitudinal learning. There was some evidence suggesting that the changes in attitudinal learning could persist over 6 months (Thomas & Cohn, 2006) and deteriorate after 1 year (Hogan & Mallott, 2005;Neville, Heppner, Louie, Thompson, Brooks, & Baker, 1996). Turning to behavioral learning, we found that 37 studies reported short-term effects (e.g., Hauenstein et al, 2010), whereas 18 studies focused on long-term behavioral consequences of diversity training (e.g., Kalev et al, 2006;Roberson et al, 2009).…”
Section: Diversity Training Outcomesmentioning
confidence: 76%
“…In sum, research on diversity training will benefit from developing theory-based training programs. (Neville, Heppner, Louie, Thompson, Brooks, & Baker, 1996) …”
Section: Not Specified 106mentioning
confidence: 99%
“…However, our finding that counselor trainees who had at least a semester of additional training after their multicultural course exhibited significantly higher competency than even those counselor trainees who had just completed a multicultural course seems to contradict some previous results. The few studies that have presented longitudinal data indicate that the effects of multicultural training remain constant after the initial postcourse increase (Neville Heppner, Thompson, Brooks, & Baker, 1996;Wang, 1998). However, with so few studies having examined long-term effects of multicultural training and the cross-sectional design of this study, it is unclear at this point if attitudes should be expected to remain constant or continue developing.…”
Section: Relation To Past Researchmentioning
confidence: 99%
“…A small but consistent set of studies has illustrated the effectiveness of counselor training courses aimed at increasing multicultural the competencies of knowledge, awareness, and skill (e.g., Diaz-Lazaro & Cohen, 2001;Neville, Heppner, Thompson, Brooks, & Baker, 1996;Wang, 1998). These assessments have included self-report measures of multicultural competency (MCC) such as the Multicultural Counseling Awareness Scale (MCAS; Ponterotto et al, 1996) or the Multicultural Awareness/ Knowledge/Skills Survey (MAKSS; D'Andrea, Daniels, & Heck., 1991).…”
Section: Multicultural Training and Outcomes Assessmentmentioning
confidence: 99%
“…Research with the MAKSS-CE has been completed with diverse samples and shown the measure to have adequate reliability and validity data (e.g. Constantine & Ladany, 2000;Neville et al, 1996). The MAKSS-CE-R also has evidence of adequate reliability and validity (Dunn et al, 2006;Kim et al, 2003).…”
Section: Measurement Construction: Refugee Torture Counseling Competementioning
confidence: 99%